Local language and culture under the burden of post-colonial dependency: africanisation of "Recuerdos del abuelo Bayebé y otros relatos bubis" by Justo Bolekia Boleká (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2021)
The problematic of local language and culture under the weight of postcolonial Western dependence is still an alarming issue. To the extent that, both at a linguistic and cultural level, it has to be faced by the production of literary materials and by the dignification of the traditional Equatorial Guinea’s heritage evoked in them. This dynamic of making African heritage visible through literature is what has characterized the works of many authors from Equatorial Guinea. Their ambition is to fight against cultural subordination. Hence, the present work aim, on the one hand, to analyze the traditional narrative strategies used in the work of Justo Bolekia Boleká, and, on the other hand, to show his process of reappropriation of traditional values in response to the “colonial wound”.
Keywords: Africanization; Justo Bolekia Boleká; Culture; Local languages; Equatorial Guinea; Post-colonialism